Operational Independence, Democratic Accountability, and Precision Policing in Indonesia - Sri Sulastri; Hadi Purnomo (Sekolah Tinggi Ilmu Kepolisian, 2026)
Indonesia’s police-governance debate is often framed as a choice between direct presidential control and full institutional separation. That binary overlooks the more precise legal question: how democratic policy direction can coexist with professional independence in case-specific policing decisions. This article examines the constitutional and administrative position of the Indonesian National Police (Polri) after Law Number 5 of 2026, using qualitative normative legal research with statutory, conceptual, and structured comparative approaches. Primary legal materials include the 1945 Constitution, the relevant People’s Consultative Assembly Decrees, the Police Law and its latest amendment, regulations on Polri and Kompolnas, and Constitutional Court Decision Number 114/PUU-XXIII/2025. Japan, Germany, and England and Wales are compared because they represent distinct arrangements for collegial buffering, territorial distribution of police authority, and an express separation between political accountability and operational command. The analysis finds that Indonesian law has strengthened professionalism, neutrality, internal supervision, and Kompolnas, while leaving the meaning and limits of Polri’s position “under the President” insufficiently specified for case-specific intervention. The article proposes a two-level institutional boundary test that distinguishes lawful democratic control over legislation, general priorities, budgets, appointments, and public accountability from prohibited directions concerning identifiable investigations, evidence assessment, or case outcomes. Its novelty lies in translating that distinction into an integrated safeguards package for Presisi: a statutory anti-interference rule, a written-direction register, reinforced external oversight, conflict-of-interest controls, merit safeguards, and reviewable implementation indicators. The proposal does not remove civilian control; it makes such control legally bounded, auditable, and compatible with evidence-based, proportionate, transparent, and procedurally fair policing.